Internationalization of Firms’ Activities and Company Union Wage Strategies - Buccella, Domenico (2014)
Using a two-country duopoly model with homogeneous goods, firms’ decisions with respect to international activities (trade vs. foreign direct investment - FDI) in the presence of company-wide unions are analyzed. If firms export, they pay trade costs per unit of the goods exported. If firms invest and set up plants abroad, they incur sunk costs. The full set of production structures that arise as sub-game perfect Nash equilibriums are derived when internationalization is feasible. The interdependence of exogenous integration costs, endogenous union wage strategies, and firms’ strategic interactions affect the equilibrium outcome: either symmetric (intra-industry trade or reciprocal FDI) or multiple symmetric (intra-industry trade and reciprocal FDI) equilibriums exist.